Philippine construction practices and their ecological effects a baseline study - Chua, Johannes Vincent F. (Quezon City College of Architecture, University of the Philippines Diliman, 2011)
Recent developments, like new local Green Building Rating Systems, show the growing awareness of environmental issues in the building industry of the Philippines. However, the hindrance to the completion of these developments is the lack of Philippine date to create quantitative and qualitative indicators to establish standards and benchmarks for Philippine conditions. The baseline study aims to alleviate this condition particularly in the practice of building. Construction practices are methods of construction, involving preferences in materials, connections and processes. These preferences comprise the current building methods in the country. However, the present Filipino construction practices seem to produce unknown ecological effects. The study has three different objectives: first, to identify the different prevailing construction practices used, second, to identify the ecological impacts these construction practices produce, and third, to compare the construction practices with local and international best practices. The study provided present conditions data for the building industry. To gather the data, a behavior type of survey was prepared and conducted among practicing contractors of the University of the Philippines Diliman Campus. This data was analyzed and evaluated of their ecological effects through comparison with local and international good construction practices, particularly prevailing Green Building Rating Systems used in the country, local codes and laws and studies from international agencies. The contractors were surveyed on eight categories, mobilization/demobilization, temporary facilities, procurement and packaging of materials, earthworks, formworks, shoring and scaffolding, utilities, waste and scrap materials, and health and safety program. The contractors were also observed during their projects to verify the presence of the practices. The study identified eighteen (18) prevailing construction practices, thirteen (13) of which have negative ecological impacts, and five (5) having positive ones. Each ecological effect was established using possible indicators. Furthermore, the baseline study proposed an initial framework for local green construction guidelines that is a starting off point for further studies. The study also proposed various recommendations for construction projects that adopted by the country such as encouraging the application of green building rating systems, introducing a greener public purchasing, conducting value management workshops and establishing a code of practice among contractors.
Vita.
Thesis (Master of Architecture)--University of the Philippines, Diliman.